Given quadratic equation - 2x^{2} + x - 6 = 0

By comparing the above equations with ax^{2 }+ bx + c we get , a = 2 , b = 1 ,c = -6

We know that , D = b^{2 }- 4ac

D = 1 - 4 × 2 × (-6) = 1 + 48 = 49 Since, D > 0 The equation have real but distinct roots .

Now, By Quadratic Formula ,

x = ( -b __+__ √D ) / 2a

x = ( -1 __+__ √49 ) / 2 × 2

x = ( -1 __+__ 7 ) / 4

x = (-1+7) / 4 OR x = (-1 -7)/4

x = 6/4 || x = -8/4

x = 3/2 or x = -2

**Hence the roots of the quadratic equation are 3/2 or -2 .**